Analisis Perilaku Lentur Balok Beton Bertulang Geopolymer menggunakan Metode Elemen Hingga - Sela, Reynaldo; Sumajouw, Dody M. J.; Mondoringin, Mielke R I A Josep (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study analyzes the flexural behavior of reinforced geopolymer concrete beams through numerical simulation based on the Finite Element Method (FEM) using ANSYS software, comparing it with conventional reinforced concrete beams. The background of this research focuses on the need for environmentally friendly construction materials, considering the high CO₂ emissions from Portland cement production. The numerical model was developed based on parameters and loading schemes from previous experimental studies, utilizing SOLID65 elements for concrete, LINK180 for steel reinforcement, and SOLID185 for supports. Simulation results show that the flexural behaviour of geopolymer beams is comparable to conventional beams in terms of load-deflection relationships, flexural capacity, and crack patterns, with deviations from experimental data generally below 10%. The patterns and propagation of cracks also exhibited similarities, starting from the tensile zone at mid-span. Furthermore, the analysis demonstrates consistency with the analytical approach based on SNI 2847:2019. This research supports the validity of using geopolymer concrete as a sustainable structural material alternative and shows that the FEM numerical method is effective in evaluating the flexural performance of concrete structural elements.